The physical activity profiles of South Asian ethnic groups in England. Issue 6 (16th December 2015) - Bhatnagar, Prachi; Townsend, Nick; Shaw, Alison; Foster, Charlie
Abstract : Background: To identify what types of activity contribute to overall physical activity in South Asian ethnic groups and how these vary according to sex and age. We used the White British ethnic group as a comparison. Methods: Self-reported physical activity was measured in the Health Survey for England 1999 and 2004, a nationally representative, cross-sectional survey that boosted ethnic minority samples in these years. We merged the two survey years and analysed data from 19 476 adults. The proportions of total physical activity achieved through walking, housework, sports and DIY activity were calculated. We stratified by sex and age group and used analysis of variances to examine differences between ethnic groups, adjusted for the socioeconomic status. Results: There was a significant difference between ethnic groups for the contributions of all physical activity domains for those aged below 55 years, with the exception of walking. In women aged 16–34 years, there was no significant difference in the contribution of walking to total physical activity (p=0.38). In the 35–54 age group, Bangladeshi males have the highest proportion of total activity from walking (30%). In those aged over 55 years, the proportion of activity from sports was the lowest in all South Asian ethnic groups for both sexes. Conclusions: UK South Asians are more active in some ways that differ, by age and sex, from White British, but are similarly active in other ways. These results can be used to develop targeted population level interventions for increasing physical activity levels in adult UK South Asian populations.